2020
DOI: 10.1111/jce.14450
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of pulmonary vein isolation ablation for atrial fibrillation conventional vs low‐ and zero‐fluoroscopy approaches

Abstract: Introduction: Radiation exposure during catheter ablation procedures is a significant hazard for both patients and operators. Atrial fibrillation (AF) ablation procedures have been historically associated with higher fluoroscopy usage than other electrophysiology procedures. Recent efforts have been made to reduce dependence on fluoroscopy during pulmonary vein isolation (PVI) ablation procedures using alternative techniques. Methods: We performed a meta-analysis of studies comparing zero or low fluoroscopy (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…In a recently published meta‐analysis of 15 studies (n = 2228) comparing low and conventional fluoroscopy approaches for RF PVI, clinical efficacy and safety was found to be similar between the low and conventional fluoroscopy arms. However, low fluoroscopy ablation procedures were associated with lower total fluoroscopy time, DAP, and even shorter procedure time 18 …”
Section: Discussionmentioning
confidence: 95%
“…In a recently published meta‐analysis of 15 studies (n = 2228) comparing low and conventional fluoroscopy approaches for RF PVI, clinical efficacy and safety was found to be similar between the low and conventional fluoroscopy arms. However, low fluoroscopy ablation procedures were associated with lower total fluoroscopy time, DAP, and even shorter procedure time 18 …”
Section: Discussionmentioning
confidence: 95%
“…The 3D‐EAM and ICE have enabled a zero or near‐zero fluoroscopy PVI with a favorable efficacy and safety 6,13,14 . However, the zero or near‐zero fluoroscopy ablation still requires experienced skills.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that major complications may not increase during a lesser fluoroscopy PVI with a visualized sheath. However, a further large‐scale study would be warranted to verify the clinical outcomes because of the rate of major complications of 0–7% in other research 14 . The price of the conventional and novel steerable sheaths is approximately equal in Japan, but the former might be lower than the latter in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the meta-analysis performed by Huang et al, comparing conventional fluoroscopy vs. low/zero-fluoroscopy PVI procedures, similar clinical efficacy and safety can be reached by the adoption of alternative imaging modalities such as 3D EAM systems, force-sensing ablation catheters and ICE. Moreover, low/zero-fluoroscopy approach was associated with shorter procedure time besides reduced fluoroscopy time and exposure ( 20 ). Visualizable SS was not used in either involved studies, however, considering the available scientific data, application of these types of SSs could help in the feasibility of the low/zero-fluoroscopy approach and improve procedural outcomes of PVI procedures.…”
Section: Discussionmentioning
confidence: 99%